The case for targeting community pharmacy‐led health improvement: Findings from a skin cancer campaign in Wales. (15th February 2016) - Pearce, Sioned; Evans, Andrew; Phelps, Ceri; Matthews, Maura; Hughes, Gail; Lewis, Ian
Abstract: The use of community pharmacies to deliver health improvement campaigns is well established. Cancer incidence is closely related to increasing levels of deprivation. Because community pharmacies are more prevalent in deprived areas there is potential for them to make an important contribution to health improvement by delivering interventions aimed at reducing cancer incidence amongst those at greatest risk. Objectives: The aims of the study were: to examine the association between high risk behaviour and deprivation and contribute evidence to the case for or against targeting cancer prevention campaigns at specific risky behaviour in areas of high deprivation. Methods: This study has an ecological design and involved retrospective analysis of data derived from 5739 sun‐safety quizzes completed by pharmacy users at 714 community pharmacies in Wales during May 2014. Results: Levels of participation in the campaign and high risk sun‐safety behaviours were higher in more deprived areas. Respondents from deprived areas had significantly lower sun‐safety knowledge. 3802 (66.2%) respondents reported 'excellent' or 'good' knowledge of behaviours which promote sun‐safety but this did not necessarily translate into how individuals behaved. 3787 (66.1%) respondents considered community pharmacies an acceptable location for the campaign and for discussing the signs and symptoms of skin cancer. Key Findings: Results show association between high risk behaviour and geographically defined deprivation adding to the case for targeting cancer prevention campaigns at specific behaviours and geographies. Conclusions: Community pharmacies appear to be acceptable locations from which to deliver health improvement campaigns in terms of participant recruitment, ease of delivery, and pharmacy user feedback.